A Swartz Model Program for the Development of Intermediate School Students’ Critical Reading Skills - Alofi , Ibrahim A. (Dirasat: Educational Sciences, 2020)
The current study aims to examine the effectiveness of a program based on Swartz’s model in the development of critical reading skills for intermediate third grade students. A quasi-experimental approach was adopted in the treatment of the study variables. A total of 65 third-grade intermediate students in Madinah took part in this study. The study sample included two groups: an experimental group (n= 33) that studies the program which is based on the Swartz’s model and a control group (n= 32) that studies the regular program. A number of results were reached, including the existence of statistically significant differences between the average performance of the experimental group and the control group in the critical reading test for the experimental group, which indicates the supremacy of the experimental group and their improvement in critical reading as a result of the use of Swartz’s model. The study put forward a number of recommendations. Primarily, it is hereby recommended that intermediate-school Arabic language teachers are trained on the use of Swartz’s model in developing with Arabic language skills. Further studies may consider replicating this study across educational levels so more solid conclusions can be reached.